ANALISIS STATUS HARA TANAH SAWAH DI KOTA METRO - Etik Puji Handayani (STIPER Dharma Wacana Metro, 2014)
The Ability of paddy soil to ensure the provision of nutrients for plants were dynamic depends on nutrient supplying power. The research was conducted on Metro City fron June until October 2011. The objective of this study was to characterize chemical properties of paddy soil. The result showed that (1) Paddy soil around Metro City classified on on acid soils, N-available low, P-available varies (low, high and very high), and K-available high, (2) The addition of lime ti inreasing siol pH should be used on the analysis of Al-dd and H-dd from each location.Keyword: Paddy Soil, Nutrients, Supplying Power